EMERGENCE OF MUPIROCIN RESISTANCE AMONG CLINICAL ISOLATES OF METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS –– A CHALLENGING THREAT TO HOSPITAL CARE IN A RURAL MEDICAL COLLEGE OF EASTERN INDIA - TANUSHREE BISWAS; MUNMUN DAS (SARKAR) (International Journal of Pharma and Bio Sciences, 2015)
Mupirocin is a topical antimicrobial agent utilized in treatment of methicillin resistant Staphylococcus aureus. Mupirocin resistance in Staphylococcus aureus is increasingly being reported in many parts of the world in the context of its widespread use. The objectives of this study were to determine the susceptibility of methicillin resistant Staphylococcus aureus clinical isolates to mupirocin to assess the prevalence of low and high level of mupirocin resistance among them, to detect their resistance to other antimicrobials and also to correlate their mupirocin susceptibility with resistance to other antimicrobials. Methicillin resistant Staphylococcus aureus isolates were tested by disc diffusion method using 5µg and 200µg mupirocin discs respectively to determine low and high level resistance to mupirocin. Susceptibility testing to other antimicrobials, including erythromycin, gentamicin, co-trimoxazole, ciprofloxacin, tetracycline, clindamycin, chloramphenicol, vancomycin and linezolid were also done. 54.12% Staphylococcus aureus isolates were found as methicillin resistant, of them 14.13% and 4.35% showed low and high level resistance to mupirocin respectively. No resistance were detected to vancomycin and linezolid. Mupirocin resistant isolates showed more susceptibility to clindamycin and tetracycline as compared to mupirocin sensitive methicillin resistant Staphylococcus aureus isolates.